Harmonizing Gold-Backed Currencies Regulatory Framework in the Global Islamic Financial System - Sidik, Heru Muara; Mulyadi, Mulyadi; Santosa , Wahyuningsih; Khan , M. Dawud Arif; Ali, Jati Kasuma (Jurnal Hukum Islam, 2025)
This study explores the legal, technological, financial, and ethical dimensions of gold-backed currencies (GBCs) to assess their viability in contemporary financial systems. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses of 78 peer-reviewed studies from Scopus and Web of Science published between 2018 and 2024, the study uncovers regulatory inconsistencies across regions, including (under Markets in Crypto-Assets regulations), ASEAN (through OJK’s gold mandate), and Saudi Arabia, thereby impeding the international adoption of blockchain technology for Shariah compliance. While blockchain technology enhances transparency and compliance through smart contracts, it also introduces cybersecurity risks and conflicts with the General Data Protection Regulation (GDPR). Furthermore, Shariah compliance continues to be a subject of contention, with Saudi Arabia raising concerns regarding the classification of intangible assets. In this regard, the review proposes the implementation of an AI-driven liquidity model framework, advocating for a tiered regulatory approach in advanced economies and the establishment of central bank safeguards in emerging markets, while ensuring ethical considerations. By leveraging GBCs, stakeholders can unlock their potential as an inclusive and resilient financial instrument. Future research endeavors should prioritize the development of AI-driven liquidity models and the execution of comparative empirical studies across various geographical regions.